Italy and the Suez Canal, from the Mid-nineteenth Century to the Cold War A Mediterranean History - Curli, Barbara (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Conceived in the 1850s and opened to navigation in 1869, the Suez Canal's construction coincided with Italy's path to unification and its first foray into nineteenth-century globalization. Since then, the history of Italy and the Canal have intertwined in many ways, throughout peace and war. This edited collection explores the fundamental technical, diplomatic and financial contributions that Italy made to the production of the Canal and to its subsequent development, from the mid-nineteenth century to the Cold War. Drawing from unpublished public and private archival sources, this book is the first comprehensive account of this long and multifaceted relationship, providing innovative perspectives on Italy's diplomatic, economic, social, colonial and cultural history. An insightful read for those studying maritime, diplomatic or Italian history, this book contributes to a growing body of research on the Suez Canal, which has largely emerged from international business, labour and social history, and offers new insights into the Euro-Mediterranean region. Barbara Curli is Professor of Contemporary History at the University of Turin, Italy. She is an editorial board member of Italia Contemporanea and is on the Scientific Board of the Fondazione Leonardo - Civiltà delle Macchine.
1 Introduction: Italy and the Suez Canal: Historical and historiographical passages from a Euro-Mediterranean perspective -- Part I. Modern infrastructures for a modern state: the Suez Canal and Italian unification -- 2 Italy's path to unification and the techno-scientific diplomacy of the Suez canal, 1855-1857 -- 3 Italian infrastructures at the time of the opening of the Suez canal -- 4 The Suez canal and Italian port cities. Local competition and global ambitions within a nation in the making (1850s-1870s) -- 5 The Suez canal and the Italian sailing fleet. Expectations, problems and alternative routes (1869-1914) -- 6 A Venice of the Desert: The successes and failures of the Suez canal in revitalizing Mediterranean trade -- Part II. Italian cultures and the Canal project.-7 Luigi Negrelli (1799-1858): a Tyrolean engineer at the heart of the Suez canal project -- 8 'This concerns the future of Italy'. The Suez canal as an opportunity: Giuseppe Sapeto and his L'Italia e il canale di Suez -- 9 The Trieste-Suez connection: how businessman and explorers reshaped the Mediterranean in the 18th and 19th centuries -- 10 'Iddio si serve mirabilmente dell'uomo per adempire i suoi altissimi fini': the Suez canal in the Italian Catholic Press in the 19th Century -- Part III. Colonial spaces, colonial encounters -- 11 Assab and the Suez canal. Traditional Networks and Imperial Agendas in the Red Sea -- 12 Credit, debt and power: Italian foreign-policy in the heavily-indebted Muslim-Mediterranean countries (1867-1914) -- 13 Sneaky Neutrality and the Mediterranean space. Weapons smuggling in Egypt during the Italo-Ottoman war, 1911-12 -- Part IV. Imperial strategies in the Mediterranean, from the mid-1860s to the Second World War -- 14 Italian Sea power and Suez. From opportunity to obsession: 1861-1943 -- 15 Connecting the two seas. Negotiating an inter-Imperial modus vivendi: Italian and Ottoman diplomacies in the Suez-Red Sea area -- 16 When two worlds collide. Britain, Italy and the Suez canal in the Fascist Era -- Part V. Work and Migration.-17The Suez canal in conversations through time: Evangelical and Waldensian transnational mobility in the Mediterranean -- 18 'Their Parents Are All Sailors and Blue-Collar Workers'. Elementary Education in the Suez canal Region at the Turn of the Century -- 19 Transnational Labour in Conflict: The Italian and Greek personnel of the Suez canal Company and the Second World War -- Part VI. Postwar Suez.-20 Leaving Egypt: Rethinking 1956 through Italian departures -- 21 Italian Catholics and the Suez crisis: between neo-Atlanticism, pacifism and third worldism -- 22 The Oil Route. Bernardo Bertolucci's filmic journey through the Suez canal.
Keywords: Italy-History.; International relations-History.; Technology; History; World politics; History of Italy; Diplomatic and International History; History of Technology; Political History